Predicting the cost of COVID-19 treatment and its drivers in Indonesia: Analysis of claims data of COVID-19 in 2020-2021 - Ryan R. Nugraha; Mutia A. Pratiwi; Ruli Endepe Al-Faizin; Ardian Budi Permana; Ery Setiawan; Yuli Farianty; Kalsum Komaryani; Hasbullah Thabrany (Health Economics Review, 2022)
Background: Recent Coronavirus Disease-19 (COVID-19) pandemic shows that health system, particularly hospital care, takes the highest toll on COVID-19. As hospital gets to manage the surge of COVID-19 cases, it is important to standardize treatment standard and package for COVID-19. Until recently, in Indonesia, COVID-19 curative package in hospital is paid using a retrospective payment system (claims system) using a per-diem rate. Quantifying standard cost using an established retrospective claims dataset is important as a basis for standard formulation for COVID-19 package treatment, should COVID-19 be accommodated into the beneft package for Universal Health Coverage (UHC) under the National Health Insurance. Methods: We estimated a standard cost for COVID-19 treatment using provider's perspective. The analysis was conducted retrospectively using established national COVID-19 claims dataset during January 2020 until 2021. Utiliz- ing individual-or-patient level analysis, claims profle were broken down per-patient, yielding descriptive clinical and care-related profle. Estimate of price and charge were measured in average. Moreover, indicators were regressed to the total charged price (in logarithmic scale) so as to fnd the predictors of cost. Results: Based on the analysis of 102,065 total claims data received by MOH in 2020-2021, there is an average claim payment for COVID-19 in the amount of IDR 74,52 million (USD 5175). Signifcant diference exists in hospital tarifs or price to the existing claims data, indicating proft for hospital within its role in managing COVID-19 cases. Claim amount predictors were found to be associated with change of claim amount, including high level of severity, hospi- tal class, intensive care room occupancy and ventilator usage, as well as mortality. Conclusion: As COVID-19 pandemic shifts towards an endemic, countries including Indonesia need to refect on the existing payment system and move towards a more sustainable payment mechanism for COVID-19. The COVID-19 payment system needs to be integrated into the existing national health insurance allowing bundled payment to become more sustainable, which can be achieved by comprehensively formulating the bundled payment package for COVID-19.
Keywords: 330; Claim payment; Retrospective payment; Medical cost; COVID-19; Indonesia